CHARACTERISATION AND SPECIATION OF CANDIDA SPECIES FROM NEONATAL SCNU AT A TERTIARY CARE HOSPITAL IN NORTHEASTERN INDIA - Madhusmita Das; Lipika Gaur (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: In the neonatal intensive care unit, Candida infections are a major source of morbidity and mortality. The incidence of neonatal candidiasis is rising, primarily due to improved survival rates for low-birth-weight newborns, preterm births, medical advancements, life support systems, relative immunodeficiency, and widespread use of broad-spectrum antibiotics. Candida albicans’ supremacy has gradually given way to nonalbicans Candida species over the last few decades. Aim and Objective: To determine the spectrum of Candida infections and to characterize the isolated species of Candida in neonatal blood samples. Materials and methodology: It was a hospital based cross sectional study carried out in the Department of Microbiology, Jorhat Medical College [JMC], for a period of one year from July 2015 - June 2016. Blood culture bottles of Neonates received in the lab were tested. Results: Out of 542 samples, 123 [22.6%] samples showed neonatal candidemia. Out of 123 isolates, 100 were identified as C.utilis [81.3%], sixteen isolates were identified as C.tropicalis[13%],five isolates were identified as C.glabrata [4%] and two isolates were identified as C.famata[1.7%]. Conclusion: Neonatal candidemia is a significant condition in our area. The current study emphasises nonalbicans Candida species as an emerging threat in neonatal candidemia.